Intestinal Microbiota Regulate Certain Meat Quality Parameters in Chicken - Lei, Jiaqi; Dong, Yuanyang; Hou, Qihang; He, Yang; Lai, Yujiao; Liao, Chaoyong; Kawamura, Yoichiro; Li, Junyou; Zhang, Bingkun (Frontiers in Nutrition, 2022)
Abstract: The existence of the intestinal microbiota-muscle axis provides the possibility to improve meat quality through the regulation of intestinal microbiota in broiler production. This study aims to explore the relationship between intestinal microbiota and water-holding capacity of muscle in broilers. According to our results, Arbor Acre broiler and Beijing-You broiler existed remarkable difference in microbiota composition. The different composition of gut bacteria evolved gradually semblable profile when the two breeds of broiler were mix raised. This consistency of microbiota induced similar water-holding capacity between Arbor Acre broiler and Beijing-You broiler. In subsequent experiment, specific intestinal microbiota structure was shaped to Arbor Acre broiler via continuous oral gavage bacteria suspension which derived from the two breeds of broiler mentioned above. Fecal microbiota from Beijing-You broiler not only increased body weight and abdominal fat rate but decreased drop losing rated of muscle in Arbor Acre broilers. And the enlarge of muscle fiber diameter caused by increased the expression of MyoD1 gene was feasible an important element to reinforce this capacity of muscle. Among five advantage genus we screened which existed in both donators and receptors broilers. Lachnoclostridium was the only one associated with all mentioned phenotypes. Importance: Higher body weight and superior meat quality in livestock imply an adequate source of protein and substantial commercial rewards. Regulating intestinal microbiota of broilers is a great potential approach to optimize commercial phenotypes. Our results indicated the profile of intestinal microbiota was capable of reconstructed by external factors and followed some changes of muscle characteristic. The cecum microbiota of native broiler has the ability to improve certain meat quality and production performance. Lachnoclostridium may serve as biomarkers to regulate body weight and drip losing rate in broiler while more research is necessary.